Sustainable growth, input factors, and technological progress in agriculture: Evidence from 1990 to 2020 in China - Tong, Wenxia; Qin, Guangke; Xu, Yanmin; Fu, Chen (Frontiers in Environmental Science, 2023)
Abstract: This paper decomposes agricultural input factors into labor, land, fertilizer, and farm machinery in 31 provinces of China from 1990 to 2020 and analyzes their contribution rates to China's agricultural growth by the stochastic frontier model. The empirical results find that the contribution rate of input factors in China's agricultural growth has weakened, with decreasing contribution rate of labor, increasing contribution rate of fertilizer and machinery, and decreasing contribution rate of the land year by year; the contribution rate of technological progress is increasing and there is room for improvement. In addition, technological progress and input factors alternately lead in the time of policy change in China. The research also shows that the prerequisite for promoting rural supply-side reform and achieving sustained agricultural growth is the need to ensure a stable supply of input factors, with a focus on promoting agricultural technological progress.